1989
DOI: 10.1182/blood.v74.1.139.139
|View full text |Cite
|
Sign up to set email alerts
|

Microenvironmental toxicity of azidothymidine: partial sparing with hemin

Abstract: Azidothymidine (AZT) is a useful drug in management of AIDS. Nevertheless, its hematologic toxicity such as anemia and neutropenia present further complications to an already compromised hematopoietic state in patients. We studied the effects of AZT on human and murine bone marrow (BM) colony growth as determined by assays of CFU-E, BFU-E, CFU-GM, and fibroblastoid stromal (CFU-Fb) colonies. Cultures were grown in methylcellulose with growth factors and scored after three- to 14-day incubation. In general, mur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

1990
1990
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…22) This causes serious hematologic toxicity such as anemia and leucopenia. 30) In combination with fluconazole, the plasma concentration of AZT glucuronide is decreased, which results in a higher plasma concentration and prolonged half-life of AZT. 31,32) Fluconazole inhibited AZT glucuronidation with 1.4 mM of Ki in HLM.…”
Section: Discussionmentioning
confidence: 99%
“…22) This causes serious hematologic toxicity such as anemia and leucopenia. 30) In combination with fluconazole, the plasma concentration of AZT glucuronide is decreased, which results in a higher plasma concentration and prolonged half-life of AZT. 31,32) Fluconazole inhibited AZT glucuronidation with 1.4 mM of Ki in HLM.…”
Section: Discussionmentioning
confidence: 99%
“…Dainiak and his colleagues (1988) also demonstrated that ZDV impairs the proliferation of human hemapoietic progenitors and that erythroid precursors are particularly sensitive. Abraham et al (1989) demonstrated that ZDV suppresses human and mouse bone marrow colony growth (CFU-E, BFU-E, CFU-GM, and CFU-Fb) and that bone marrow colonies from mice were more sensitive than those from humans. They further showed that some of the inhibitory effects of ZDV could be overcome by the addition of hemin to the cultures.…”
Section: Study Daymentioning
confidence: 99%
“…The antiviral properties of heme in the inhibition of replication of HIV‐1 as well as the enhancement of the antiviral action of AZT‐TP in bone marrow cultures from AZT‐resistant patients have recently been demonstrated [3]. Earlier studies have demonstrated that heme can exert a protective effect against the bone marrow toxicity of AZT‐TP [4–6]. Recent studies have also manifested that metalloporphyrins inhibit HIV‐1 RT activity in a noncompetitive manner with respect to deoxythimidine triphosphate and markedly enhance the inhibitory effect of AZT‐TP on HIV‐1 RT [7].…”
mentioning
confidence: 99%